SOME ASPECTS OF PLEA AGREEMENT IN CROATIAN MISDEMEANOUR PROCEEDINGS IN DOMESTIC VIOLENCE CASES (EU and comparative law issues and challenges series (ECLIC), 2024)
This paper is dedicated to the issue of violence against women and domestic violence in the context of the plea agreement of the parties and the procedural position of the victim in these proceedings. Therefore, this paper first analyses the European legal standards that weave the positive legal basis for the limitation of alternative ways of solving cases in the domain of domestic violence. The two pillars of the Convention's supervisory mechanism are then considered, which ensure the effective implementation of the proclaimed standards, with special reference to the results of the evaluation of the legal systems of the member states of the Convention from the perspective of the victim's right to effective investigation and the prohibition of alternative dispute resolution processes in the context of entering into plea agreements in cases of violence against women and domestic violence. Finally, the current normative framework of the Misdemeanour Act on the procedure for entering into a plea agreement and sanction is critically analysed, shortcomings and inconsistencies of the current procedural solutions are pointed out, and proposals are made for the future aimed at reviving international legal standards in the Croatian Misdemeanour Act.